Apakah Tri Hita Karana dan Pancasila Dua Ideologi yang Identik? (Satu Kajian Ontologis) - Sukadi Sukadi (Purwadita : Jurnal Agama dan Budaya, 2020)
Balinese Hindu people in general believes Tri Hita Karana (THK) as their ideology in social and religious life.  THK ideology teaches Hindus people in Bali to live in harmony in order to achieve happiness both physically and mentally.  The happiness of living in a society and religion originates from efforts to establish harmonious relationship between humans and The One Almighty God (Parahyangan).   between and among human beings (Pawongan),  and between humans and their natural environment (Palemahan).  In the life of the nation and state as part of Indonesian society, the Balinese Hindu community also implements the Pancasila ideology.  By the ideology of Pancasila, the Balinese Hindu society upholds and implements the values of Pancasila which consist of five sila. Why can Balinese Hindu society implement these two ideologies without experiencing conflict.  The answer is because these two ideologies are both open ideologies and have a relevant ontological basis. Keywords: Tri Hita Karana, Parahyangan, Pawongan, Palemahan, dan Pancasila